A Multi-layer Scenario Analysis for Sustainable International Transport - Barry Ubbels; Caroline Rodenburg; Peter Nijkamp (Tinbergen Institute, 2000)
It is clear that the future of the transport sector is fraught withuncertainties, as the system can be influenced by many factors thatcan develop in various ways. The aim of this paper is to gain insightinto the future development of the transportation sector. It presentsthe development of the transport sector based on four globalisationscenarios. On three different scale levels (global, European andDutch) four future images of the transportation market areconstructed. The expected implications of these scenarios are mappedout in a clear description of the various relevant aspects, such asmodal split and spatial organisation. In addition, this paper alsoprovides empirical insight into expected transport flows of passenger(passenger kilometres) and freight transport (ton-kilometres) in2020, based on data from 1995. It appears that globalisation leads inall scenarios and on each scale level to a considerable growth oftransported volumes.
Keywords: 330; Globalisierung; Grenzüberschreitender Verkehr; Nachhaltige Entwicklung; Welt